Reservoir Characterization of Lacustrine Environment, Doba Basin, Southern Chad: Radioactive Sand Delineation - MS Nur Fathiha, SZ Lo, AS Ahmed Mohamed, . (2017)
The contribution of lacustrine environment as the hydrocarbon reservoir has been widely known. However, despite of its growing importance, the lacustrine petroleum geology has received far less attention than marine due to its sedimentological complexity [3]. This study therefore aims at developing an understanding of the unique aspects of lacustrine reservoirs which eventually impact the future exploration decisions.